Oral Selinexor as Maintenance Therapy After First-Line Chemotherapy for Advanced or Recurrent Endometrial Cancer - Vergote, Ignace; Pérez-Fidalgo, Jose Alejandro; Hamilton, Erika Paige; Valabrega, Giorgio; Van Gorp, Toon; Sehouli, Jalid; Cibula, David; Levy, Tally; Welch, Stephen; Richardson, Debra L; Guerra, Eva M; Scambia, Giovanni; et al. (Journal of clinical oncology, 2023)
PURPOSE: Selinexor inhibits exportin-1 (XPO1) resulting in nuclear accumulation of tumor suppressor proteins including p53 and has clinical activity in endometrial cancer (EC). The primary end point was to assess progression-free survival (PFS) with once-weekly oral selinexor in patients with advanced or recurrent EC. PATIENTS AND METHODS: ENGOT-EN5/GOG-3055/SIENDO was a randomized, prospective, multicenter, double-blind, placebo-controlled, phase III study at 107 sites in 10 countries. Patients 18 years or older with histologically confirmed EC were enrolled. All had completed a single line of at least 12 weeks of taxane-platinum combination chemotherapy and achieved partial or complete response. Patients were assigned to receive 80 mg oral selinexor once weekly or placebo with 2:1 random assignment (ClinicalTrials.gov identifier: NCT03555422). RESULTS: Between January 2018 and December 2021, 263 patients were randomly assigned, with 174 allocated to selinexor and 89 to placebo. The median PFS was 5.7 months (95% CI, 3.81 to 9.20) with selinexor versus 3.8 months (95% CI, 3.68 to 7.39) with placebo (hazard ratio [HR], 0.76 [95% CI, 0.54 to 1.08]; two-sided P = .126), which did not meet the criteria for statistical significance in the intent-to-treat population. Incorrect chemotherapy response stratification data for 7 (2.7%) patients were identified. In a prespecified exploratory analysis of PFS in audited stratification data, PFS for selinexor met the threshold for statistical significance (HR, 0.71; 95% CI, 0.499 to 0.996; two-sided P = .049). Furthermore, patients with the TP53 wild-type (wt) EC had a median PFS of 13.7 and 3.7 months with selinexor and placebo. The most common grade 3 treatment-related adverse events were nausea (9%), neutropenia (9%), and thrombocytopenia (7%). CONCLUSION: The significance level for PFS was only met in the audited analysis. However, a preliminary analysis of a prespecified exploratory subgroup of patients with TP53wt EC showed promising results with selinexor maintenance therapy.
Keywords: Endometrial Neoplasms; dvojitá slepá metoda; Triazoles; Hydrazines; Prospective Studies; hydraziny; lidé; Female; ženské pohlaví; Double-Blind Method; triazoly; Humans; nádory endometria; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; prospektivní studie